Effect of Tocotrienol Rich Fraction (TRF) Administration on Blood Glucose and Cholesterol in Streptozotocin Induced and High Fat Diet Rats - Irene Simangunsong; Dewi Pertiwi; Aminah Dalimunthe; Vivi Asfianti (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder with a continuously increasing global prevalence and remains a major health problem, characterized by hyperglycemia and dyslipidemia, including elevated Low Density Lipoprotein (LDL) and decreased High Density Lipoprotein (HDL) levels. This study aimed to evaluate the effect of tocotrienol rich fraction administration on blood glucose levels and lipid profile in rats induced with streptozotocin and a high fat diet. The study used 24 white rats divided into six groups: a negative control group, a positive control group treated with glibenclamide, and four treatment groups receiving tocotrienol rich fraction at doses of 50, 100, 200, and 400 mg/kg body weight. The measured parameters included blood glucose, HDL, and LDL levels. The results show that tocotrienol rich fraction significantly reduces blood glucose levels and improves the lipid profile compared to the negative control group. The highest dose demonstrates the most optimal effect and approaches that of the positive control. Tocotrienol rich fraction increases HDL levels and decreases LDL levels in a dose dependent manner. These findings indicate that tocotrienol rich fraction significantly lowers blood glucose levels and improves lipid profile in streptozotocin induced and high fat diet rats in a dose dependent manner. Therefore, tocotrienol rich fraction has potential as an alternative therapeutic agent for diabetes mellitus with dyslipidemia.